Egg colouration predicts brood size, telomere length and body condition of spotless starling fledglings. (4th July 2018) - Soler, Juan J.; Ruiz‐Castellano, Cristina; Figuerola, Jordi; Martínez‐de la Puente, Josué; Ruiz‐Rodríguez, Magdalena; Tomás, Gustavo
Abstract : Understanding the impressive interspecific variation in avian eggshell colouration has attracted the attention of evolutionary ecologists for more than a century. Several functional explanations predict positive covariation between eggshell pigmentation and phenotypic quality of nestlings. We test this prediction in spotless starlings Sturnus unicolor by using biometric measurements and telomere length of hatchlings and fledglings as proxies of phenotypic quality. Female spotless starlings lay immaculate blue‐green eggs, a sexually selected signal directed to males. Pigmentation predicts positive associations with concentration of antioxidants and testosterone in the yolk and with paternal provisioning effort during nestling growth. Eggshell pigmentation (blue‐green chroma) is not associated with telomere length of hatchlings, which suggests weak maternal effects on this trait. However, we find negative associations of eggshell colouration with both body condition and telomere length of fledglings. Moreover, we find positive associations between eggshell colouration and clutch size, which suggests that sibling competition is higher in nests with more coloured eggshells. Previous works demonstrated that level of sibling competition is positively related to telomere erosion and, thus, the detected negative associations between eggshell colouration, body condition and telomere length of fledglings would reflect higher level of competition in nests with more coloured eggshells. We therefore speculate with the possibility that females that lay larger clutches also lay more coloured eggshells that elicit increased paternal provisioning effort and, thus, raise larger broods at the expense of telomere erosion of their offspring.